86.4k views
25 votes
If 9x+4y=−3 is a true equation, what would be the value of 6(9x+4y)?

User Marslo
by
6.0k points

2 Answers

12 votes

Answer:

-18

Explanation:

Given

  • 9x + 4y = -3

We need to evaluate 6(9x + 4y).

Substitute the value of 9x + 4y in the expression.

  • 6(9x + 4y)
  • 6(-3)
  • -18
User Webspirit
by
6.0k points
4 votes

Answer:

-18

Explanation:

9x + 4y = -3 (Given)

Multiply both sides of the equation by 6, we find:

6(9x + 4y) = 6(-3)

-> 6(9x + 4y) = -18

User Baao
by
6.4k points